Optical bistability of a plexcitonic system consisting of a quantum dot near a metallic nanorod - Tayebeh Naseri; Nader Daneshfar (Journal of Theoretical and Applied Physics)
Abstract Optical response of a complex nanodimer comprising a semiconductor quantum dot via Coulomb interaction to a metal nanorod is analyzed theoretically. Optical bistability (OB) behavior of a coherently coupled exciton-plasmon (plexcitonic) hybrid system under a laser field is investigated. The bistable exciton population in a hybrid metal–semiconductor nanodimer response is shown, and it could be pointed out that OB behavior is strongly influenced by various parameters such as size of metal nanoparticle, interparticle distance as well as intensity of probe laser field. We show that OB can be observed for a plexcitonic system and depends strongly on the type of the metals which are good candidates for plasmonic applications. The numerical calculations show the gold nanorod exhibits significant optical bistability. The result promises various applications in the field of all-optical information processing at the nanoscale, the most basic of them being the optical switching, optical memory, optical transistor and optical logic.